PELAKSANAAN PENDIDIKAN DAN PELATIHANPEGAWAI APARATUR SIPIL NEGARA DI LINGKUNGAN SEKRETARIAT DAERAH KOTA PEKANBARU TAHUN 2016 - Sepwiraka Adhi Ganda; Erman M (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
State Civil Apparatus Education (SCA) is an education conducted for SCA to improve the personality, knowledge, ability in accordance with the requirements of position and work as SCA. SCA training is part of education conducted for Civil Servants as State Civil Apparatus (SCA) to improve their knowledge and skills in accordance with the demands of its requirements as State Civil Apparatus (SCA). To improve the ability of State Civil Apparatus (SCA) within Pekanbaru City Government, especially at the Regional Secretariat of Pekanbaru City in this case by doing the development of employees that is by conducting Education and Training Position that leads to attitudes and dedication oriented to the interests of Society, Nation and State improve the efficiency, effectiveness and quality of the tasks performed in a spirit of cooperation and responsibility, in accordance with the work environment and organizationThis research was conducted at the Regional Secretariat of Pekanbaru City. The purpose of this study is to know the Implementation of Education and Training of Civil State Employees in the Regional Secretariat of Pekanbaru. The method used in this research is descriptive qualitative method. The researcher tries to explain the implementation of the Training of State Civil Servant Apparatus so that the performance of the Civil State Apparatus Officer can be known. Data collection techniques in this study using interview and documentation techniques. Based on interviews to all informants and based on data obtained by researchers when conducting research, it can be concluded that the Implementation of Education and Training of Civil State Employees in the Regional Secretariat of Pekanbaru City does not run optimally. First, the difficulty of arranging study time between more experienced employees (senior) with new employees to do training in a field of work. Secondly, Participants sometimes can not directly apply the knowledge or skills acquired from the exercise.Kata Kunci:Pelaksanaan, Pendidikan dan Pelatihan, Aparatur Sipil Negara